Child Abuse as Portrayed in Delia Owen's Where The Crawdads Sing - Cahyani, Gita Senja Ayu; Supsiadji, Mateus Rudi (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
Child abuse occurs when a child is hurt or abused by an adult. This can happen in various ways, impacting the child's body, cognition, and emotions. This study discusses the kind of child abuse and the impact of child abuse in Delia Owens' Where the Crawdads Sing. This study uses the child abuse theory by Christiane Sanderson and takes a psychological approach as it examines real-life phenomena. A qualitative approach is used as a method of research. The analysis reveals that Kya experiences physical abuse, emotional abuse, and neglect, primarily inflicted by her father and further exacerbated by the abandonment of her parents and siblings. Kya endures physical abuse through beatings and threats from her father, emotional abuse through his dismissive and degrading behavior, and neglect as she is left to fend for herself in extreme poverty and isolation. These abuses have long-term effects on her physical and psychological health. Kya is malnourished because her parents abandoned her. Psychologically, she suffers from deep anxiety and a profound lack of trust as a result of repeated trauma and isolation. In conclusion, Kya's experiences with physical abuse, emotional abuse, and neglect emphasize the severe and lasting impacts of child abuse on an individual's physical and mental well-being. The novel highlights how these traumatic experiences shape Kya's interactions with family and society. Childhood traumatic experience that made Kya become the person who has anxiety.